DEVELOPMENT OF TITANIUM DIOXIDE NANOTUBE FOR HYDROGEN SENSING APPLICATION - SORIADI, NURHIDAYA (2015)
Detection of hydrogen is crucial for industrial process control and medical applications where the presence of hydrogen in breath indicates a different type of health problems particularly in infants. In recent years, interest in breath analysis for clinical purposes has increased. As the demand for hydrogen sensors and hydrogen analyzers grows, a better performed sensor with high sensitivity would be critical especially for medical applications. The titanium dioxide nanotube structure is chosen as an active component in the gas sensor because of its highly sensitive electrical resistance to hydrogen over a wide range of concentrations. The objective of the work is to fabricate and develop good quality titania nanotubes with specific characteristics as the sensing element for detection of very low concentration of hydrogen.